The application of the triple bottom line approach to sustainability assessment: The case study of the UK automotive supply chain - Susana Garrido Azevedo; Miguel Barros (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: The objective of this paper is to assess the level of sustainability of the UK automotive supply chain considering simultaneously the three dimensions of sustainability (economic, social and environmental) representing the Triple Bottom Line (TBL) approach. Design/methodology/approach: The assessment of the automotive SC' sustainability is based on the framework proposed by Salvado, Azevedo, Matias and Ferreira (2011) and uses the Simple Additive Weighting (SAW) method to aggregate economic, environmental and social indicators into a unique index. A case study on the UK automotive industry is used and the data do perform this study is collected from the sustainability reports of the UK' automotive companies. Findings and Originality/value: The proposed framework represents an important benchmarking tool, offering managers the possibility for assessing the sustainability behaviour of its supply chain and compare it with other supply chains. Once identified the dimension of sustainability where the company or the supply chain is worst performer managers can work closer to their supply chain' partners in order to improve the performance of those dimension of sustainability. Research limitations/implications: One limitation of the suggested approach is related to the ambiguity of the sustainability' indicators selection and the definition of weights for each sustainability dimension. Practical implications: The assessment of the SC sustainability by using the suggested framework to compute a SC sustainability index offers managers an opportunity for assessing the level of sustainability of each individual company and the corresponding SC in a very easy way. It also represents an opportunity for improving company performance. In this way managers can use the information on the sustainability index to help adjust their company's behaviour and improve their economic, social and environmental performance. Originality/value: The proposed framework represents a contribution in the area of index construction and a valuable component of organizational management systems and monitoring programs.
Keywords: 650; sustainability; framework; composite index; supply chain; automotive industry